PENGARUH ARUS KAS OPERASI, PERTUMBUHAN PENJUALAN DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SEKTOR INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2022–2024 - Kelsiva Awalia Zilayonta; Mar'atus Solikah; Sigit Puji Winarko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of operating cash flow, sales growth, and liquidity on financial performance of industrial sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024. The background of this research is based on challenging economic conditions following the COVID-19 pandemic, including inflationary pressures, rising interest rates, and global uncertainty affecting corporate performance. This study employs a quantitative approach with explanatory research method. Samples were selected using purposive sampling technique, yielding 36 companies with a total of 108 observations. Data analysis employed multiple linear regression using SPSS version 22, encompassing descriptive statistical tests, classical assumption tests, t-test, F-test, and coefficient of determination (R²). The results reveal that operating cash flow and liquidity significantly affect financial performance, while sales growth does not. Simultaneously, all three variables significantly influence the financial performance of industrial sector companies listed on the IDX.